Aliphatic silver functionalized hydrogel as well as preparation method and application thereof
By adding specific compounds to the hydrogel, aliphatic silver functionalized hydrogel was developed, which solved the problem of insufficient immune regulation in the body by existing hydrogels, and achieved effective improvements in acute tissue damage and chronic wound healing. .
Patent Information
- Application Number
- CN202411445734.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-18
AI Technical Summary
The immune regulation effect of existing hydrogels in the body has not been fully studied, and it is difficult to effectively solve the problems of acute tissue damage and chronic wound healing.
Develop an aliphatic silver functionalized hydrogel, which improves its conductivity, antibacteriality and Mechanical properties.
By significantly improving the wound healing process, promoting angiogenesis, collagen synthesis, macrophage polarization and granulation tissue formation, quickly resolve acute tissue damage and improve the chronic wound healing process.
Smart Images

Figure CN119463038A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedicine, and in particular relates to an aliphatic silver functionalized hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogels have long been of interest for skin wound dressings due to their unique properties, such as moisture retention and extracellular matrix-like structure. They can also serve as delivery vehicles, increasing their versatility. Many hydrogels have been developed to modulate immunomodulatory cells and promote immune responses in wound healing. These hydrogels strive to strike a balance between inflammatory cell infiltration, modulating macrophage polarization, enhancing cell proliferation and migration, and controlling collagen remodeling by manipulating their physicochemical properties. The effects of physical properties such as dimensionality, hardness, porosity, morphology, electrical properties, and wettability on immune responses have been elucidated. However, most of these studies have been limited to laboratory experiments conducted in vitro, ignoring the immunomodulatory role played by hydrogels in vivo. Summary of the invention
[0003] The present invention provides an aliphatic silver functionalized hydrogel and a preparation method and application thereof, so as to solve one or more technical problems existing in the prior art.
[0004] The first aspect of the present invention is to provide an aliphatic silver functionalized hydrogel.
[0005] The second aspect of the present invention is to provide a method for preparing the aliphatic silver functionalized hydrogel described in the first aspect of the present invention.
[0006] The third aspect of the present invention is to provide the use of the aliphatic silver functionalized hydrogel described in the first aspect of the present invention in the preparation of drugs.
[0007] The raw materials of the aliphatic silver functionalized hydrogel in the first aspect of the present invention include acrylamide carboxy betaine, acrylamide sulfonyl betaine, silver nanowires and carboxymethyl cellulose.
[0008] The acrylamide carboxybetaine and the acrylamide sulfobetaine are both zwitterions. Experimental verification shows that the two zwitterions can play a synergistic role in the hydrogel, have better wound healing ability, and the performance is far superior to the hydrogel containing only a single zwitterion. Silver nanowires significantly improve the conductivity of the hydrogel, which is beneficial to wound healing. At the same time, the strong antibacterial properties help prevent wound infection and maintain a sterile healing environment. In addition, unlike general silver nanoparticles, the silver nanowires have a one-dimensional structure and can be better integrated into the hydrogel matrix, thereby providing superior mechanical reinforcement, making the hydrogel stronger and more flexible. The highly fibrillated nature of carboxymethyl cellulose (CMC) greatly enhances the mechanical properties and structural stability of the hydrogel.
[0009] In some application embodiments of the first aspect of the present invention, the structural formula of the acrylamide carboxy betaine is as shown in formula (I):
[0010] Formula (I).
[0011] In some application embodiments of the first aspect of the present invention, the preparation method of acrylamide carboxybetaine is: cooling N-(3-dimethylaminopropyl)methacrylamide to 0°C, adding β-butyrolactone dropwise, maintaining a nitrogen atmosphere of 0-4°C and stirring until the reaction is completed, filtering the crude product, washing with ether, and drying under vacuum.
[0012] In some application embodiments of the first aspect of the present invention, the structural formula of the acrylamide sulfobetaine is as shown in formula (II):
[0013] Formula (II).
[0014] In some application embodiments of the first aspect of the present invention, the preparation method of acrylamide sulfobetaine is: dissolving N-(3-dimethylaminopropyl)methacrylamide in dimethylformamide, gradually adding 1,3-propane sultone dissolved in N,N-dimethylformamide, stirring at room temperature until the reaction is completed, filtering the crude product, washing with hexane, and drying at room temperature to obtain the product.
[0015] In some application embodiments of the first aspect of the present invention, the carboxymethyl cellulose is modified carboxymethyl cellulose. The preparation method of the modified carboxymethyl cellulose is: dissolving acrylic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 4-dimethylaminopyridine in dimethyl sulfoxide, reacting for 24 hours, adding to a phosphate buffer solution in which carboxymethyl cellulose is dissolved, and the reaction product is subjected to continuous dialysis and freeze-dried to obtain the modified carboxymethyl cellulose.
[0016] The preparation method described in the second aspect of the present invention comprises the following steps: 1) preparing the acrylamide carboxy betaine represented by formula (I) and the acrylamide sulfonyl betaine represented by formula (II) respectively; 2) dissolving the carboxymethyl cellulose in water, adding the silver nanowires, and stirring thoroughly; 3) adding the acrylamide carboxy betaine and the acrylamide sulfobetaine, and adding an initiator and an accelerator after they are completely dissolved; 4) After gelation is achieved, immersing the hydrogel in deionized water to remove impurities, thereby obtaining the aliphatic silver functionalized hydrogel.
[0017] In some application embodiments of the second aspect of the present invention, in step 3), the mass ratio of the acrylamide carboxy betaine to the acrylamide sulfonyl betaine is 1:1.
[0018] In some application embodiments of the second aspect of the present invention, in step 3), the initiator is ammonium persulfate; preferably, the accelerator is tetramethylethylenediamine.
[0019] The application described in the third aspect of the present invention refers to the use of the aliphatic silver functionalized hydrogel for preparing a drug for promoting wound healing.
[0020] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages: Through in vivo experiments, the efficacy of the aliphatic silver functionalized hydrogel in rapidly resolving acute tissue injury, such as a full-thickness skin defect model, was not only verified but also demonstrated by significantly improving the wound healing process. Specific findings include specific improvements in wound healing by promoting angiogenesis, collagen synthesis, macrophage polarization, and the formation of granulation tissue. The ability of the aliphatic silver functionalized hydrogel to address acute tissue injury and improve the chronic wound healing process makes it an ideal candidate for a variety of wound healing applications and other biomedical uses. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is the XRD pattern of the aliphatic silver functionalized hydrogel; Figure 2 is a SEM image of the aliphatic silver functionalized hydrogel; Figure 3 is an EDX spectrum of the aliphatic silver functionalized hydrogel; Figure 4 is the FT-IR spectrum of the aliphatic silver functionalized hydrogel; Figure 5 This is a photo of wound healing in Example 3; Figure 6 is a bar graph of wound closure rate in Example 3; Figure 7 Staining images of macrophage polarization in wound sections. DETAILED DESCRIPTION
[0022] The present invention is described in detail below through examples to facilitate understanding of the present invention by persons skilled in the art. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Non-essential improvements and adjustments made to the present invention by persons skilled in the art based on the above-mentioned invention content should still fall within the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products, and the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0023] Example 1, preparing the aliphatic silver functionalized hydrogel.
[0024] 1. Synthesis of Acrylate-CMC: 0.1 mL of acrylic acid, 0.3 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC·HCl), and 0.04 g of 4-dimethylaminopyridine (DMAP) were dissolved in 2 mL of dimethyl sulfoxide (DMSO) and allowed to react for 24 hours. Subsequently, the solution was added to 30 mL of carboxymethyl cellulose (CMC) in phosphate buffer. The reaction was carried out at room temperature for another 24 hours. The resulting product was subjected to continuous dialysis with a molecular weight cutoff of 7 kDa for 24 hours and then lyophilized to obtain acrylate-CMC (A-CMC).
[0025] 2. Synthesis of acrylamide carboxybetaine: Under nitrogen, 1 g of N-(3-dimethylaminopropyl)methacrylamide was cooled to 0°C. Then, 0.48 mL of β-butyrolactone was added dropwise under nitrogen atmosphere, and the mixture was stirred at 0-4°C for 24 hours under nitrogen. After the reaction was completed, the crude product was filtered, washed with ether, and dried under vacuum to obtain a white solid, which was acrylamide carboxybetaine (ACB).
[0026] 3. Synthesis of acrylamide sulfobetaine: 1 g of N-(3-dimethylaminopropyl)methacrylamide and 1.16 g of 1,3-propane sultone were dissolved in 5 mL of dimethylformamide (DMF), respectively, and then the two solutions were gradually mixed. The mixture was stirred at room temperature for 2 hours. After the reaction was completed, the crude product was filtered and washed three times with hexane. Subsequently, it was dried at room temperature to obtain a white powder, namely acrylamide sulfobetaine (ASB).
[0027] 4. Preparation of the aliphatic silver functionalized hydrogel: 1 g of A-CMC was dissolved in 24 mL of water, and then 1 mL of silver nanowire solution (purchased from Merck, Chile) was added dropwise while ensuring adequate stirring. Subsequently, 0.25 g of ACB and 0.25 g of ASB were added to the mixture. After the components were completely dissolved, the free radical polymerization process was initiated by adding 10 mg of ammonium persulfate (APS) and 5 L of tetramethylethylenediamine (TEMED) as initiator and promoter, respectively. The resulting hydrogel sample was carefully transferred to a Petri dish, where the polymerization process was allowed to proceed at 70 °C for 24 h. After gelation, the hydrogel was immersed in deionized water to remove any remaining unreacted substances and impurities, thereby ensuring the purity of the final product.
[0028] Example 2, characterization of the aliphatic silver functionalized hydrogel.
[0029] The phase purity of the catalysts was determined using wide angle X-ray diffraction (W-XRD) patterns, which were performed using a Bruker D8 diffractometer with Cu Kα radiation, scanning from 10° to 80° with a Bragg angle (2 θ ). Field emission scanning electron microscopy (FE-SEM) mapping was performed using a Gemini SEM 300. The functional groups of the hydrogels were analyzed using Fourier transform infrared spectroscopy. NMR spectra were recorded using a Bruker AVANCE 400 MHz spectrometer using deuterated solvents.
[0030] Figure 1The XRD pattern of the aliphatic silver functionalized hydrogel prepared in Example 1. It is noteworthy that the peaks at 21.1°, 29.4°, 31.9° and 34.1° indicate crystal planes, highlighting the highly fibrillated nature of CMC, indicating its potential for enhanced mechanical properties and structural stability. In addition, there are four obvious diffraction peaks at abscissas 37.8°, 44.3°, 64.3° and 77.4°, corresponding to the face-centered cubic (FCC) patterns of (111), (200), (220) and (311) silver nanowires, respectively. This observation is consistent with the standard data obtained (JCPDS file number 04-0783 provided by ASTM). The presence of these silver nanowires plays a multifaceted role in improving the properties of the hydrogel. First, the silver nanowires significantly improve the electrical conductivity of the hydrogel. The enhanced conductivity is particularly beneficial for wound healing, where electrical stimulation can promote cell migration and proliferation, thereby accelerating the healing process. Secondly, the potent antibacterial properties of silver are crucial in this case. Silver nanowires ensure the sustained release of silver ions, which effectively destroys the cell wall of bacteria and interferes with their metabolic processes. This sustained antibacterial effect helps prevent wound infection and maintain a sterile healing environment. The presence of silver nanowires significantly enhances the conductivity and antibacterial effect of the aliphatic silver functionalized hydrogel, making it an ideal candidate material for advanced wound care applications. XRD analysis confirmed the successful incorporation of silver nanowires into the aliphatic silver functionalized hydrogel. The integration of silver not only improves the functional properties of the hydrogel, but also helps create a favorable environment for rapid wound healing and tissue regeneration.
[0031] Figure 2 : is a SEM image of the aliphatic silver functionalized hydrogel. It can be observed that the silver nanowires are evenly distributed in the hydrogel network. Figure 3 The corresponding EDX spectra provide the atomic and weight percentages of Ag and other elements present in the hydrogel. The highly fibrous morphology of the aliphatic silver functionalized hydrogels, coupled with the introduction of silver nanowires, enhances the stability of the hydrogel surface, making it suitable for cell proliferation and migration. This fibrous structure is key to promoting wound healing. It mimics the natural extracellular matrix and provides a scaffold to support new blood vessel formation by encouraging endothelial cells to attach and form capillaries. The fiber network also increases the surface area for cell attachment and promotes cell proliferation. In addition, the fibers help macrophages shift to an M2 phenotype, reduce inflammation and aid tissue repair. Although the SEM images mainly show a fiber morphology without visible pores, this structure effectively supports the essential cellular processes of wound healing and tissue regeneration. In addition, these hydrogels exhibit effective oxygen permeability and have bactericidal properties, making the aliphatic silver functionalized hydrogels particularly suitable for treating wounds.
[0032] Figure 4FT-IR spectroscopy was used to characterize the functional groups of the aliphatic silver functionalized hydrogel. 3253 cm -1 The absorption peak at 2914 cm corresponds to the stretching vibration of free hydroxyl (OH) in CMC, indicating that the presence of hydroxyl contributes to the hydrophilicity and water retention of the hydrogel. -1 The absorption band at 2367 cm -1 A characteristic absorption peak was observed at 1572 cm -1 and about 1298~1414 cm -1 The absorption peaks correspond to carboxylic acid (COO - ) groups, confirming the presence of carboxylic acid groups that play a key role in the zwitterionic nature and ion exchange capacity of the hydrogel. In addition, the -1 and 1034 cm -1 The presence of the absorption peak at is attributed to sulfate (SO3 - ) groups. These peaks confirm the incorporation of sulfate groups, which contribute to the charge distribution of the hydrogel and enhance the interaction with biomolecules. FT-IR results confirm the successful incorporation of carboxylates, sulfates, and other related functional moieties into the hydrogel matrix. These functional groups are critical to the performance of the hydrogel, affecting its hydrophilicity, ionic interaction capabilities, and overall stability, making it very suitable for use in wound healing and tissue regeneration.
[0033] Example 3, evaluation and analysis of the effect of the aliphatic silver functionalized hydrogel on the wound healing process.
[0034] Two control hydrogels were prepared according to the preparation method of Example 1. The first one did not contain ASB, and the prepared hydrogel was called "ACB / Ag / CMC"; the second one did not contain ACB, and the prepared hydrogel was called "ASB / Ag / CMC".
[0035] Male KM mice (n=24, weight=30±3 g) aged 6-8 weeks were used, authorized by the Experimental Animal Center of Shantou University. All organisms were housed in a controlled environment (temperature 25±1℃; 12h / 12h light-dark cycle; humidity 60±10%) with unrestricted access to water and complete free diet. After anesthesia, two circular wounds with a diameter of 0.5 cm were made on the shaved back of each mouse. The 24 injured mice were divided into NC, ACB, ASB, and ACS groups, with 6 mice in each group. The wound area was photographed with a digital camera to establish baseline measurements. The wounds were then treated in different ways according to the group: the NC group used PBS solution to treat the wounds, the ACB group used a 7 mm diameter disc-shaped ACB / Ag / CMC hydrogel to cover the wounds, the ASB group used a 7 mm diameter disc-shaped ASB / Ag / CMC hydrogel to cover the wounds, and the ACS group used a 7 mm diameter disc-shaped aliphatic silver functionalized hydrogel to cover the wounds. Subsequently, the hydrogel dressing was covered with a Tegaderm transparent dressing to prevent infection and wrapped with a thin layer of self-adhesive bandage to prevent splint injury. If the treatment effect of two wounds in the same mouse was inconsistent, it was considered an invalid sample. The images of the mice were captured on days 0, 4, 7, 10, 14, and 17 after treatment, and the wound size was calculated with a digital vernier caliper. The closure rate of the wound was evaluated by measuring the wound area using Image-Pro Plus software to depict the wound edge. The wound closure rate (RW) was calculated using the following formula: RW=(S0-S N ) / S0*100% Among them, S0 is the wound area on day 0; S N is the wound area on day N.
[0036] Figure 5 The wound healing pictures of each experimental group. Figure 6 The figure shows the results of using Image-Pro Plus software to measure the wound area to depict the wound edge to evaluate the wound closure rate. As can be seen from the figure, compared with the NC group, the other three groups showed significantly improved wound regeneration behavior, and there were no obvious signs of inflammation or infection near the wound area. The proliferation of the new epidermis extended to the core of all hydrogel-treated wounds, resulting in a reduction in the injured area. At each time point, the hydrogel containing acrylamide zwitterions showed a significantly high wound closure rate under natural conditions. The final relative wound area of the ACS group was 2.1% compared with the ACB group (11.0%), the ASB group (10.09%) and the NC group (17.8%). On day 14, there was a significant difference between the NC group and the ACS group, with a p value of less than 0.01 ("*" indicates p < 0.05). In general, the aliphatic silver functionalized hydrogel significantly improved wound regeneration.
[0037] Example 4: Immunohistochemical staining was used to detect the effect of the hydrogel on wound healing.
[0038] In Example 3, each group of mice was anesthetized with chloral on the 14th day and euthanized by cervical dislocation. The damaged tissue was harvested, preserved with 10% formalin solution and inserted into paraffin, and wound tissue sections with a thickness of 4 microns were prepared. The obtained sections were respectively measured for macrophage polarization using M1 macrophage marker CD68 and M2 marker CD163. The stained sections were observed using a laser scanning confocal microscope (LSCM) from Zeiss, Germany.
[0039] Figure 7 Figure 2 shows the staining of macrophage polarization in wound sections. The analysis in the figure shows that the ACS group showed a higher tendency to transform into M2 macrophages on day 7 compared with natural healing and other hydrogel dressings. This observation is derived from the significant increase in green in the figure. The finding of M2 / M1 macrophage expression once again confirms the positive effect of the aliphatic silver functionalized hydrogel in the wound regeneration process. These results show that the hydrogel not only promotes cell proliferation, but also plays an important role in regulating the immune response, which is crucial for effective healing.
[0040] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. An aliphatic silver functionalized hydrogel, characterized in that: The raw materials include acrylamide carboxybetaine, acrylamide sulfobetaine, silver nanowires and carboxymethyl cellulose.
2. The aliphatic silver functionalized hydrogel according to claim 1, characterized in that: The structural formula of the acrylamide carboxy betaine is shown in formula (I): Formula (I).
3. The aliphatic silver functionalized hydrogel according to claim 2, characterized in that: The preparation method of acrylamide carboxybetaine is as follows: N-(3-dimethylaminopropyl)methacrylamide is cooled to 0°C, β-butyrolactone is added dropwise, a nitrogen atmosphere of 0-4°C is maintained and stirred until the reaction is completed, a crude product is filtered, washed with ether, and dried under vacuum to obtain the product.
4. The aliphatic silver functionalized hydrogel according to claim 1, characterized in that: The structural formula of the acrylamide sulfobetaine is shown in formula (II): Formula (II).
5. The aliphatic silver functionalized hydrogel according to claim 4, characterized in that: The preparation method of acrylamide sulfobetaine is as follows: dissolving N-(3-dimethylaminopropyl)methacrylamide in dimethylformamide, gradually adding 1,3-propane sultone dissolved in N,N-dimethylformamide, stirring at room temperature until the reaction is completed, filtering the crude product, washing with hexane, and drying at room temperature to obtain the product.
6. The aliphatic silver functionalized hydrogel according to claim 1, characterized in that: The carboxymethyl cellulose is modified carboxymethyl cellulose. The preparation method of the modified carboxymethyl cellulose is as follows: acrylic acid, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and 4-dimethylaminopyridine are dissolved in dimethyl sulfoxide, react for 24 hours, and then added into a phosphate buffer solution containing carboxymethyl cellulose. The reaction product is subjected to continuous dialysis and freeze-dried to obtain the modified carboxymethyl cellulose.
7. The method for preparing the aliphatic silver functionalized hydrogel according to any one of claims 1 to 6, characterized in that: Includes steps: 1) preparing the acrylamide carboxy betaine and the acrylamide sulfobetaine respectively; 2) dissolving the carboxymethyl cellulose in water, adding the silver nanowires, and stirring thoroughly; 3) adding the acrylamide carboxy betaine and the acrylamide sulfobetaine, and adding an initiator and an accelerator after they are completely dissolved; 4) After gelation is achieved, immersing the hydrogel in deionized water to remove impurities, thereby obtaining the aliphatic silver functionalized hydrogel.
8. The preparation method according to claim 7, characterized in that: Step 3) The mass ratio of the acrylamide carboxy betaine to the acrylamide sulfonyl betaine is 1:
1.
9. The preparation method according to claim 7, characterized in that: Step 3) The initiator is ammonium persulfate; preferably, the accelerator is tetramethylethylenediamine.
10. Use of the aliphatic silver functionalized hydrogel according to any one of claims 1 to 6 in the preparation of a drug for promoting wound healing.